Phenotypic and Functional Properties of Porcine Dedifferentiated Fat Cells during the Long-Term Culture In Vitro. (18th May 2015) - Peng, Xuewu; Song, Tongxing; Hu, Xiaoming; Zhou, Yuanfei; Wei, Hongkui; Peng, Jian; Jiang, Siwen
Abstract : It has been proved that terminally differentiated mature adipocytes possess abilities to dedifferentiate into fibroblast-like progeny cells with self-renewal and multiple differentiation, termed dedifferentiated fat (DFAT) cells. However, the biological properties of DFAT cells during long-term culture in vitro have not been elucidated. Here, we obtained fibroblast-like morphology of porcine DFAT cells by ceiling culture. During the dedifferentiation process, round mature adipocytes with single large lipid droplets changed into spindle-shaped cells accompanied by the adipogenic markers PPAR γ, aP2, LPL, and Adiponectin significant downregulation. Flow cytometric analysis showed that porcine DFAT cells displayed similar cell-surface antigen profile to mesenchymal stem cells (MSCs). Furthermore, different passages of porcine DFAT cells during long-term culture in vitro retained high levels of cell viabilities (>97%), efficient proliferative capacity including population doubling time ranged from 20 h to 22 h and population doubling reached 47.40 ± 1.64 by 58 days of culture. In addition, porcine DFAT cells maintained the multiple differentiation capabilities into adipocytes, osteoblasts, and skeletal myocytes and displayed normal chromosomal karyotypes for prolonged passaging. Therefore, porcine DFAT cells may be a novel model of stem cells for studying the functions of gene in the different biological events.